Adulteration of raw milk in the rural areas of Barisal district of Bangladesh (Bangladesh Journal of Animal Science, 2013)
The study was undertakento detect the type of adulterants and preservatives added to the incoming fluid milk from rural areas to the Barisal city of Bangladesh. Total fifty milk samples were collected from five different entry points of Karapure, Dabdopia, Shaestabad, Goriarpar and Khanpura of Barisal district where ten samples were taken from each entry point. The results indicated that, 100% of the milk samples were adulterated with water irrespective of collection points and months. Cane sugar, powdered milk and starch were detected as 26.0, 14.0 and 12.0% in the milk samples, respectively. Two types of preservatives namely formalin and sodium bicarbonate were detected in the fluid milk from the study areas. Out of all samples, 10.0% was adulterated with formalin and 20.0% with sodium bicarbonate. However, none of the samples contained either hydrogen peroxide or borax. There was a positive relationship between day temperature and intensity of adding preservatives to the fluid milk. As the day temperature increased, the number of preservative positive samples also increased in a linear fashion and vice versa. It could therefore be inferred that, the consumers need to be more cautious regarding the quality of raw milk specially in summer season.DOI: http://dx.doi.org/10.3329/bjas.v41i2.14126Bang. J. Anim. Sci. 2012. 41 (2): 112-115